Modelo de Heisenberg XXZ para ondas de spin em baixa dimensão - Silva, Wanêssa Façanha da (2021)
Low-dimensional systems have attracted much attention lately due to materials such as graphene and carbon nanotubes. Such systems have great potential for technological applications, in particular the creation of electronic devices due to their specific electronic properties. In this sense, the study of other systems in low dimension becomes urgent, as for exemple, the study of magnetic properties of materials at low dimensionality and with the development of this field of research we will have a better understanding of the phenomena related to magnetism. There are several curious sunjects to be investigatedin magnetic systems such as behavior of spin waves wich is important for the study of spintronic. Spintronics has generated inumerous researchs on the development new apparatus and magnetic memories, such as the research of magnetic graphene, for example, which has the development of new spintronic components (which store data using the spin of the electron instead of its charge). The process of forming a magnetic graphene is given by placing the graphene on a layer of magnetic insulator, a material that is an electrical insulator but with magnetic properties. Due to the grat impact potencial of the magnetic researches in the technological life that wesurround, we aim at this work to study the behavior of spin waves in two-dimensional ferromagnetic systems using Hamiltonians of Heisenberg XXZ. Such Hamiltonian is characterized by having J x = J y 6 = J z . For two-dimensional systems we consider here networks decorated. Such decorations are introduced to generate networks with more than one basic atom in the unit cell of the system to study the richness of the spectrum of spin waves due to these changes. At first deal with a superimposition of square networks where the displacement of these networks depends on control parameters α and β. We also use the superposition of a square on a hexagonal network. We also analyzed the overlap between two triangular networks.